Case studies on BPO and ITO at large captive operations in India. - Penter, Kevan; Pervan, Graham; Wreford, John (Information Systems and Innovation Group, 2008)
The past decade has seen explosive growth in offshore Business Process Outsourcing (BPO) to India by US and European companies. However, Australian companies have been slower to take advantage of this trend towards Globally Distributed Work (GDW). This appears surprising given sixteen years of unbroken expansion of the Australian economy that have created near full employment and skills shortages that can be addressed by offshore outsourcing. However, a large-scale survey of domesticIT outsourcing in Australia reported that failure rates are higher than has been recognized in the literature, while practitioner sources report widely varying success rates with offshore IT and business process outsourcing. With little in the way of theory or models to guide management decision-making, perhaps the underparticipation by Australian companies is less surprising.An Australian Bank (ANZ) and a UK airline (British Airways) provide two examples of companies that have created value for shareholders through successful implementation of Globally Distributed Work. Both have utilized a captive business processing operation in India for over a decade, but have pursued contrasting BPO strategies. British Airways expanded the scope of its operation by taking on BPOwork for other companies in the travel sector, introduced private equity and then conducted a successful initial public offering. ANZ has expanded the size of its captive operations, integrated it more tightly into the parent company and is now capitalizing on the operational benefits offered by its Bangalore unit.While captive IT Enhanced Services (ITES) operations appear to offer advantages in terms of managing knowledge, they also require significant senior management commitment over 2-3 years to deliver business benefits and mentor the emergence of a cadre of ?culturally agile? managers. And yet the captive model appears least researched. The authors are using these and other case studies to develop a decision3 making framework that will assist companies to make effective investments in GDW,including making effective choices about engagement options and risk management.